Requirements, legal consequences of withdrawal and criminal types of abstract danger - Ramos Quiñones, Myriam Stephanie (Unaciencia, Revista de Estudios e Investigaciones, 2020)
The application of the paradigm of aggression, understood as the one in which there is an element of the objective type, the danger or the actual injury to the protected legal good, which are absent in the criminal types of abstract danger and that is why not only violates procedural guarantees and fundamental rights, but also the dogmatic category of material unlawfulness, in addition to undermining the withdrawal as an acquittal legal excuse, regarding which seeks to identify the requirements and legal consequences of the withdrawal and criminal types of danger abstract, through the application of juridical and analogical hermeneutics according to positions from the doctrine and jurisprudence, which finally leads us to find the withdrawal as a figure applicable to other criminal types and the non-punitive behavior of asbest danger from the theory of crime and iter criminis.
Keywords: Array; Array; Array